Approaches to the Canonical Subjectivity of the Family - Arroba Conde, Manuel Jesús (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The doctrine of the Magisterium on the family is very abundant, while there are many gaps in canonical discipline that overshadow its real consideration as a subject of rights in the Church. This reflection aims to propose ways to overcome this gap, clarifying the juridical impact of the doctrine of the magisterium, both in the interpretation of the norms in force and in the possible integration of its gaps. The exhortation Amoris laetitia, as well as the texts of the recent synodal path on the topic, are the main sources of the approach to the theme.
Keywords: family rights; Norma missionis; protection of the family; family mission